Gender as risk factor for mouth breathing and other harmful oral habits in preschoolers - Lara Jansiski Motta; Thays Almeida Alfaya; Analúcia Ferreira Marangoni; Raquel Agnelli Mesquita Ferrari; Kristianne Porta Santos Fernandes; Sandra Kalil Bussadori (Universidade Estadual de Campinas, 2015)
Aim: To analyze associations between the mouth-breathing pattern and other harmful oral habits among preschoolers. Methods: An observational, cross-sectional study was carried out involving 198 children from 3 to five 5 of age. A questionnaire, clinical evaluation and specific tests (mirror and water tests) were used for confirmation of the mouth-breathing pattern. Results: Mean age of the participants was 4.13 ± 0.8 years and 57.1% were male. A total of 87.4% exhibited one or more harmful oral habits. Harmful habits were more common in the male gender (61.8%); this association was statistically significant (p<0.001). Mouth breathing was the most prevalent habit (49%), followed by biting/sucking on objects (33.3%). Regarding gender, statistically significant associations were found for bottle feeding (p=0.02) and nail biting (p=0.02). Mouth breathing was associated with biting on object (p=0.00), pacifier use (p=0.02) and thumb sucking (p=0.00). Conclusions: The results of the present study suggest that mouth breathing is significantly associated with biting/sucking on objects, pacifier use and thumb sucking in preschoolers and that the occurrence of harmful oral habits is more prevalent among the male gender. Early diagnosis and intervention should be established in order to avoid future consequences involving the orofacial region.